THE EFFECTIVENESS OF USING THE LABORATORY IN LEARNING SCIENCE - Ainun Ilmi Wahidah; Alif Mardiana; Siti Anisatul Iriani; Amalia Safitri; Asya Fikriyatun Nihaya; Mufidatul Nafiah (PEDAGOGIK : JURNAL PENDIDIKAN, 2021)
The science that studies nature and its processes are called Science. When learning about Science, the laboratory has an essential role in growing students' experimentation abilities and increasing students' enthusiasm for learning. This study aims to describe and determine the effectiveness of the use of laboratories in science learning at SMPN 2 Lumajang. This study uses an approach with the interview method. This research was carried out at SMPN 2 Lumajang, which involved subject science teachers at the SMPN. The results showed that the science laboratory at SMPN 2 Lumajang had two rooms: a laboratory room and a storage room. Judging from the aspect of the laboratory space, the science laboratory of SMPN 2 Lumajang still needs to be improved a bit, such as a space to store tools and materials, and there is no preparation room to make preparations before the practicum begins. The existing facilities and infrastructure influence the effectiveness of the use of laboratories in the learning process. With complete facilities and infrastructure, student learning activities in observations will run smoothly.